Contesting categories: cross-border marriages from the perspectives of the state, spouses and researchers. Issue 2 (25th January 2021) - Moret, Joëlle; Andrikopoulos, Apostolos; Dahinden, Janine
ABSTRACT: Marriages that involve the migration of at least one of the spouses challenge two intersecting facets of the politics of belonging: the making of the 'good and legitimate citizens' and the 'acceptable family'. In Europe, cross-border marriages have been the target of increasing state controls, an issue of public concern and the object of scholarly research. The study of cross-border marriages and the ways these marriages are framed is inevitably affected by states' concerns and priorities. There is a need for a reflexive assessment of how the categories employed by state institutions and agents have impacted the study of cross-border marriages. The introduction to this Special Issue analyses what is at stake in the regulation of cross-border marriages and how European states use particular categories (e.g. 'sham', 'forced' and 'mixed' marriages) to differentiate between acceptable and non-acceptable marriages. When researchers use these categories unreflexively, they risk reproducing nation-centred epistemologies and reinforcing state-informed hierarchies and forms of exclusion. We suggest ways to avoid these pitfalls: differentiating between categories of analysis and categories of practice, adopting methodologies that do not mirror nation-states' logic and engaging with general social theory outside migration studies. The empirical contributions of the Special Issue offer new insights into a timely topic.